The Influence of Transformational and Transactional Leadership Styles on Employee Performance (Case Study at PT Perkebunan Nusantara 1 Regional 7, Kedaton District, Bandar Lampung City) - Nababan, Farida; Rinova, Dora (Journal of Environmental Economics and Sustainability, 2025)
This study examines the impact of transformational and transactional leadership styles on employee performance at PT Perkebunan Nusantara 1 Regional 7. Employee performance is a crucial factor in achieving organizational goals, and leadership style plays a significant role in shaping motivation and productivity. Using a quantitative approach, data were collected through questionnaires distributed to 80 employees across four divisions. The findings indicate that transformational leadership positively influences employee motivation and engagement, while transactional leadership ensures task completion through structured reward and penalty mechanisms. The study concludes that a combination of both leadership styles leads to optimal employee performance, balancing innovation with efficiency.